2006
DOI: 10.1002/mrd.20472
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and sperm regulatory peptides regulate ovulation in the oyster Crassostrea gigas

Abstract: For more than six decades, several studies have shown that genital products to entering the mantle cavity via the incurrent siphon, initiate in oyster, strong and rhythmic contractions of the adductor muscle (AM). In order to characterize the regulatory peptides capable of triggering AM contractions, we focused on the identification of putative myotropic peptides from genital products. Two experimental approaches were developed. The first one, based on a mass spectrometry screening of the male genital products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…C. gigas (Bernay et al, 2006, Stewart et al, 2014. Similar to the C. gigas, we found the Sg-APGWa in the visceral ganglia.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…C. gigas (Bernay et al, 2006, Stewart et al, 2014. Similar to the C. gigas, we found the Sg-APGWa in the visceral ganglia.…”
Section: Discussionmentioning
confidence: 50%
“…In the oysters, it has been demonstrated that the tetrapeptide APGWa plays a role in the reproduction of Crassostrea gigas female oysters, where it can induce in vitro adductor muscle contraction followed by oocyte release (Bernay et al, 2006). GnRH is a well-known reproductive regulator in vertebrates, but has also been found in the CNS of bivalve molluscs (Pazos andMathieu, 1999, Nakamura et al, 2007).…”
mentioning
confidence: 96%
“…3B and C). Since APGWamide controls the activity of various muscles involved in reproductive and non reproductive processes in various molluscs including the oyster (Van Golen et al, 1995;Henry et al, 1997;Henry et al, 2000;Bernay et al, 2006), the possibility of APGWamide or related peptides (Favrel and Mathieu, 1996) to activate Cg-GnRH-RII-L and Cg-GnRH-RII-S is worth being investigated. Deorphanization of these receptors via the application of reverse endocrinology/ pharmacology approaches will definitely elucidate this point.…”
Section: Possible Nature Of the Endogenous Ligand For Cg-gnrh-rii-l Amentioning
confidence: 99%
“…To evaluate Vam metalloprotease production of the resulting transconjuguant, ECPs were subjected to MS and MS/MS analyses, as previously described [17].…”
Section: Protein Identification By Peptide Mass Fingerprintingmentioning
confidence: 99%